1994
DOI: 10.1002/ca.980070305
|View full text |Cite
|
Sign up to set email alerts
|

In vivo location of the human vermiform appendix

Abstract: The anatomic position of the appendiceal tip is cited in many surgical and anatomical texts as being fixed in the retrocecal position in as many as two-thirds of cases studied. The reference most often quoted to support this observation is Wakeley (1933), but this frequency did not correspond to the clinical experience of the surgical staff at the authors' institution. Accordingly, a prospective survey of the in vivo location of the vermiform appendix was undertaken over a 6-month period. T h e results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Two studies reported the frequency of the appendiceal position in the normal and inflamed appendix groups, although it did not find a statistically significant difference between the two groups (9,19). However, our results revealed a statistically significant difference between the normal and inflamed subgroups in the preileal, postileal, subileal, and subcecal positions (Table 1).…”
Section: Resultscontrasting
confidence: 75%
“…Two studies reported the frequency of the appendiceal position in the normal and inflamed appendix groups, although it did not find a statistically significant difference between the two groups (9,19). However, our results revealed a statistically significant difference between the normal and inflamed subgroups in the preileal, postileal, subileal, and subcecal positions (Table 1).…”
Section: Resultscontrasting
confidence: 75%
“…Subjects with any gross abnormalities of abdominal organs, fibrosis, kinking or adhesions, and history of abdominal surgery were excluded. Following resection of the anterior abdominal wall, the position of the base of vermiform appendix was determined using the schema derived by [ 13 ] ( Figure 1 ). Representative photographs were taken using a Fujifilm A235 digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…This is a problem seen with open appendectomies as well [14], but stresses the need for careful laparoscopic dissection and identification of landmarks prior to appendiceal division. Fortunately, the tip of the appendix usually lies free in the peritoneal cavity [15] rather than being behind the cecum, minimizing this risk.…”
Section: Complications and Conversionsmentioning
confidence: 99%